How to Report: Wrist MRI - Ng, Wing Hung Alex; Griffith, James Francis; Ng, Isaac Sung Him (Seminars in Musculoskeletal Radiology, 2021)
Knowledge of the imaging anatomy of the wrist is essential for reporting magnetic resonance imaging (MRI). This familiarity should include the carpal bones, tendons (extensor and flexor compartments), triangular fibrocartilage complex (TFCC), intrinsic and extrinsic ligaments, and nerves, especially the median and ulnar nerves. Limitations of MRI in visualizing these structures, particularly the intrinsic ligaments and the TFCC, need to be considered. This article outlines the main features to comment on when reporting common conditions of the wrist on MRI, with some examples of terminology that can be used to describe these abnormalities.
Keywords: magnetic resonance imaging; wrist; tendon; triangular fibrocartilage complex; ganglion